Quaternary research in Indonesia
1 online resource
Keywords: Written for researchers, university lecturers and advanced undergraduate and postgraduate students in all fields of archaeological and anthropological study, this collection features new research from different excavation sites around Indonesia together with pioneering expert analysis. Groundbreaking new theories on early colonization feature alongside a thorough and up-to-date examination of field methods and techniques, and valuable insight into human development in Indonesia and beyond. Focused on Java and Sulawesi, these research findings highlight importantrecent advances in quaternary research. Results from a cave excavation in Southern Java providea much-needed long-term palaeoclimatic record, based on a lowland pollen sequence from Central Java, while thecontributionsfrom South Sulawesi include a pioneering archaeobotanical analysis, a new hypothesis on the earliest human colonisation of this island, and an attempt to reconstruct preceramic human biological population affinities. In addition, the little-known archaeology of the tiny island of Roti is presented and discussed here, with particular attentiononprehistoric survival in an impoverished island environment.